Cytotoxic and anthelmintic potentials of the leaf extracts of Saccharum spontaneum Linn. (Asia-Pacific Journal of Science, Mathematics, and Engineering, 2015)
Saccharum spontaneum Linn., locally known as "talahib", is a ubiquitous Philippine medicinal weed. Several parts of this plant have been utilized in traditional medicine for a number of applications. In this study, the decoction and the hexane-soluble and chloroform-soluble extracts were investigated for their cytotoxic and anthelminitc potentials. From the brine shrimp lethality test, the results showed that all extracts have negligible cytotoxic activities. The results of the anthelmintic assay, meanwhile, showed that the organic extracts exhibited more significant potentials against E. euginiae compared to the decoction. Particularly, the chloroform-soluble extract displayed slightly faster time than the hexane-soluble extract in bringing paralysis on the test organisms. The hexane-soluble extract, on the other hand, gave faster mean time in killing the organisms and its time, hence bioactivity, was even remarkably comparable to that of mebendazole, the positive control. Overall, the organic extracts of S. spontaneum, especially its low-polar components, proved to have promising potentials as anthelmintics.